Dampak Meditasi dan Mindfulness terhadap Struktur dan Fungsi Otak yang Berhubungan dengan Pengurangan Kecemasan - Marfita Hikmatul Aini (JURNAL ILMIAH NUSANTARA, 2024)
This research explores the impact of meditation and mindfulness on brain structure and function and their effect on reducing anxiety. Using neuroimaging technology such as fMRI, the study looked at changes in brain structure and neural activity in individuals who practiced meditation and mindfulness. The results showed that meditation and mindfulness practices significantly affected brain areas associated with emotion regulation and anxiety, including the amygdala, prefrontal cortex, and anterior cingulate cortex. These findings provide new insights into the neurobiological mechanisms behind the benefits of meditation and mindfulness in reducing anxiety.